(untitled) (Bangladesh Journal of Nuclear Medicine, 2023)
Melorheostosis is an atypical sclerosing bone dysplasia also known as "candle bone disease," "melting wax syndrome," or "Leri disease," with an incidence rate of less than one in every million. The diagnosis is usually made by the radiographic appearance of "dripping candle wax" on the affected bone cortex. We describe the case of a 35-year-old male patient who presented with a long history of different joint swelling, notably in the small joints of the right hand, left foot, and ankle. He was thoroughly investigated to rule out all other possible causes of swelling before being diagnosed with melorheostosis with osteopoikilosis based on radiological patterns. The patient was referred to our institute for a bone scan, which not only showed correlation with X-ray findings but also revealed involvement of the axial skeleton, which is a rare incidence in this disorder. Bangladesh J. Nuclear Med. 25(2): 147-150, 2022